Virtual tutors and the learning of the statistics course in the students of the Faculty of Accounting Sciences of the National University of Callao - De La Cruz Gaona, Efrain Pablo (2023)
The desire of each one of the students of the Faculty of Accounting Sciences is the mastery of each one of the subjects of the curricular mesh, and as future professionals, it is essential that they develop skills during their study time at the university. One of the most popular resources to achieve this goal is the use of Virtual Tutors through ICTs that contribute to improving academic performance; Under perspective, the objective of this research work is to determine the relationship between the use of Virtual Tutors and the learning of statistics in the students of the Faculty of Accounting Sciences of the National University of Callao. The work carried out consists of a quantitative approach with a descriptive and correlational methodological design, where a questionnaire was used to collect the opinion about the virtual tutors to later contrast with the qualifications obtained during the 2021-A academic semester. The results obtained showed for Specific Hypothesis 1 a correlation of 0.707, for Specific Hypothesis 2 a correlation of 0.674, and for Specific Hypothesis 3 a correlation of 0.601, concluding with the General Hypothesis a correlation of 0.688; In each case, there was a positive and significant correlation, which shows that the use of Virtual Tutors is related to student learning in the statistics course.